Security of Cloud Computing - Qunying Sun; Zhiyuan Hu (Dianxin kexue, 2013)
Cloud security has been widely considered as the key factor restricting its development since the cloud computing technology emerged.The insecure factors of cloud computing system and the secure factors which cloud computing brings were presented and discussed.It was pointed out that cloud security depended on the validate deployment of the security policy.Cloud computing system is not less secure than native environment，as long as the right agreement is signed with cloud provider.Finally，the proposal of security policy was provided from both the cloud provider domain and the cloud user domain to ensure the security of cloud computing system.